Perancangan Jaringan Nirkabel untuk Infrastruktur Monitoring Deformasi Bendungan Sermo - Addin Suwastono; Bambang Sutopo; Litasari (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2012)
Wireless local area networks is used by Sermo’s GNSS-CORS to renew its reference position from Department of Engineering Universitas Gadjah Mada’s CORS.The problem is, that wireless local area network should meet the bandwidth requirement and the operation should not break the frequency usage regulation in Indonesia.This reseach was conducted to study the bandwidth needs of Sermo’s dam deformation monitoring system, to design the topology, and calculating EIRP of all wireless network link in the system that meet the regulations of the Ministry of Communications and Information Republik of Indonesia. Wireless local area networks was built to connect Sermo, Faculty of Engineering Universitas Gadjah Mada and Balai Besar Wilayah Sungai Serayu Opak’s office.Design implementation and testing of broadband wireless equipment at unlicence frequency of 2.4 GHz (Motorola PTP 100) and 5.8 GHz (Motorola Motorola PTP and PTMP 5750AP/5760SM 58 300) resulted in 2.22 Mbps bandwidth that is much greater than that required, 128.7 kbps, and the average round trip delay of 19.2 ms. Antenna alignment information can be used as a reference for wireless communications equipment maintenance.